Meta Analysis the Effect of Physical Activity on Survival Life in Breast Cancer Patients - Ketaren, Enge Surabina; Murti, Bhisma; Widyaningsih, Vitri (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Physical activity has a positive role in breast cancer risk. Physical activity intensity is often expressed as metabolic equivalents (METs) and the analytic guidelines for international physical activity questionnaires define low activity as 4 METs and high activity as 8 METs. This study aims to estimate the effect of physical activity on the survival of breast cancer survivors based on a number of previous similar studies.Subjects and Method: This study is a systematic review and meta-analysis study. The articles used in this study were obtained from several databases including PubMed, Science Direct, Google Scholar, and Springer Link. The articles used in this study were those published from 2000-2020. The population in the study were breast cancer survivors with an intervention in the form of high physical activity. Comparison, namely low physical activity, and an outcome in the form of survival. Keywords for searching articles are as follows: